Pharmacokinetic/pharmacodynamic investigation of raltegravir with or without lamivudine in the context of HIV-1 pre-exposure prophylaxis (PrEP). (14th May 2021) - Herrera, Carolina; Lwanga, Julianne; Lee, Ming; Mantori, Suna; Amara, Alieu; Else, Laura; Penchala, Sujan Dilly; Egan, Deirdre; Challenger, Elizabeth; Dickinson, Laura; Boffito, Marta; Shattock, Robin; et al.
Abstract: Background: To characterize their potential use in pre-exposure prophylaxis (PrEP) we compared the pharmacokinetics of raltegravir and lamivudine in genital tissue against ex vivo tissue infection with HIV-1. Methods: Open-label trial of 36 HIV-negative females and males randomized to 7 days raltegravir 400 mg twice daily and 7 days raltegravir 400 mg+lamivudine 150 mg twice daily (after washout), or vice versa . Blood, saliva, rectal fluid, rectal tissue, vaginal fluid and vaginal tissue were sampled at baseline and on and off PrEP during a total of 12 days, for pharmacokinetics and antiviral activity via ex vivo HIV-1BaL challenge. Ex vivo infectivity was compared with baseline. The trial has been registered in https://clinicaltrials.gov/ with the identifier NCT03205566. Results: Steady state for both drugs was reached by day 4. Dosing with raltegravir alone provided modest ex vivo HIV protection with higher drug levels in rectal tissue and vaginal tissue than in plasma on and off PrEP. Off PrEP, plasma and vaginal concentrations declined rapidly, while persisting in the rectum. On PrEP, the highest lamivudine concentrations were in the rectum, followed by vaginal tissue then plasma. Lamivudine washout was rapid in plasma, while persisting in the rectum and vagina. Raltegravir/lamivudine increased ex vivo protection on and off PrEP compared with raltegravir alone, reaching maximum protection at day 2 in rectal tissue and at day 8 in vaginal tissue. Conclusions: Raltegravir 400 mg+lamivudine 150 mg showed high levels of ex vivo HIV protection, associated with high drug concentrations persisting after discontinuation in vaginal and rectal compartments, supporting further investigation of these agents for PrEP.